An Impact Crater Origin for the InSight Landing Site at Homestead Hollow, Mars: Implications for Near Surface Stratigraphy, Surface Processes, and Erosion Rates. Issue 4 (21st April 2020) - Warner, N. H.; Grant, J. A.; Wilson, S. A.; Golombek, M. P.; DeMott, A.; Charalambous, C.; Hauber, E.; Ansan, V.; Weitz, C.; Pike, T.; Williams, N.; Banks, M. E.; et al.
Abstract: The InSight mission to Mars landed within Homestead hollow on an Early Amazonian lava plain. The hollow is a 27‐m‐diameter, 0.3‐m‐deep quasi‐circular depression that shares morphologic and sedimentologic characteristics to degraded impact craters. Unlike the intercrater plains outside of the hollow, the interior lacks cobbles and is dominated by loose sand, granules, and pebbles. Fresher craters near the landing site exhibit meter‐scale bedforms in their ejecta and on their floors due to sediment trapping. The sedimentology of the interior fill of Homestead hollow suggests similar trapping. The hollow falls along a morphologic continuum that requires low rates of rim degradation and fill. Crater degradation rates (rim erosion plus filling) in the landing site decline nonlinearly through time from 10 −2 to 10 −4  m/Myr as craters evolve to a hollow‐like form. Rim erosion rates are lower initially, at 10 −3  m/Myr, but converge with degradation rates to 10 −4  m/Myr. This implies that while filling plays an important role soon after crater formation, it is limited in later stages. Crater statistics indicate that the bulk of the fill occurred in the first ~50 Myr for Homestead hollow . The estimated maximum age of the hollow is ~400 to 700 Myr. This requires near‐zero fill aggradation and long‐term soil stability for the bulk of the crater's history. Fill stability manifests in Homestead hollow as a ~5‐ to 10‐cm‐thick duricrust, formed by exchanges of atmospheric water vapor with soil. The estimated degradation in the hollow requires ~2 to 3 m of sedimentary fill beneath the lander. Plain Language Summary: The Interior Exploration using Seismic Investigation, Geodesy and Heat Transport (InSight) mission to Mars landed in western Elysium Planitia. The landing site consists of a smooth, flat surface that is unique relative to the surrounding rockier plains. Observations from orbital satellite imagery indicate that InSight landed inside of an almost circular depression in the landscape. Here we evaluate the shape and form of this small circular depression and compare it against nearby degraded impact craters. We conclude that InSight landed inside a very old crater that has filled in with windblown sediment and slope debris from the crater wall. We also estimate that the crater has been sitting on the landscape, experiencing extremely slow degradation, for approximately 400 to 700 Myr. The crater origin for the depression has implications for our understanding of the materials that exist immediately beneath the lander and the results from the two geophysical instruments onboard InSight, the Seismic Experiment for Interior Structure (SEIS) and Heat Flow and Physical Properties Package (HP 3 ). Key Points: InSight landed within a 27‐m‐diameter, 0.3‐m‐deep, degraded impact crater called Homestead hollow Homestead hollow has a maximum age of 400 to 700 Myr. Degradation rates were two orders of magnitude higher in first 50 Myr after impact Homestead hollow is filled with up to 3 m of loose infill that is composed of sand and pebbles. The hollow fill is capped by a duricrust